History of cancer in Peru - Lastres, Juan B. (1956)
Cancer as rheumatism or tuberculosis. are as old as humanity. In the first two tracks are in antediluvian animals, proving that predate the appearance of man on earth. Thus a tumor in the vertebrae of Apatosaurus and a deforming spondylitis in the vertebrae of a esmilodón, corresponding to the Pleistocene of California is discovered. In Peru, apart from two case studies on this disease, the eighteenth century, Paul Petit, the other nineteenth century, José Manuel Valdés, have not done a historiographical study of this disease, to determine their age and mortality it causes. Precise will resort to heuristic to find traces of their passage through the ages